Językowy wymiar paternalizmu – na przykładzie interakcji lekarz – pacjent i urzędnik – klient - Rutkowski, Mariusz (Forum Lingwistyczne, 2016)
Lingual Dimension of the Paternalism – on the Examples of Doctor – Patient and Clerk – Client Interaction In the paper, the issue of paternalism in the institutional talks is presented. The main features of paternalism as a communication strategy are shown sketchy. The author analyses two talks: a medical consultations and an institutional talk in the office. On these examples some of the basic manifestations of paternalism are presented, among them the ignoring of the patient`s voice, doctor`s domination including his knowledge regarding the patient`s individual feelings, using of the informal phrase “ty” (“you”), using of diminutive forms. As the result, the voice of patient/client is outgrown or muted, and at the same time the voice of the institution is dominating, and even strengthened. Key words: paternalism, asymmetry in communication, doctor – patient interaction, clerk – client interaction, conversation analysis